Combining T2 measurements and crusher gradients into a single ASL sequence for comparison of the measurement of water transport across the blood–brain barrier. Issue 5 (30th November 2020) - Petitclerc, Léonie; Schmid, Sophie; Hirschler, Lydiane; van Osch, Matthias J. P.
Abstract : Purpose: Arterial spin labeling can be used to assess the transition time of water molecules across the blood–brain barrier when combined with sequence modules, which allow a separation of intravascular from tissue signal. The bipolar gradient technique measures the intravascular fraction by removing flowing spins. The T2 ‐relaxation‐under‐spin‐tagging (TRUST) technique modulates the TE to differentiate between intravascular and extravascular spins based on T2 . These modules were combined into a single time‐encoded pseudo‐continuous arterial spin labeling sequence to compare their mechanisms of action as well as their assessment of water transition across the blood–brain barrier. Methods: This protocol was acquired on a scanner with 9 healthy volunteers who provided written, informed consent. The sequence consisted of a Hadamard‐encoded pseudo‐continuous arterial spin labeling module, followed by the TRUST module (effective TEs of 0, 40, and 80 ms) and bipolar flow‐crushing gradients (2, 4, and ∞ cm/s). An additional experiment was performed with TRUST and a 3D gradient and spin‐echo readout. Results: Gradients imperfectly canceled the intravascular signal, as evidenced by the presence of residual signal in the arteries at early postlabeling delays as well as the underestimation of the intravascular fraction as compared with the TRUST method. The TRUST module allowed us to detect the transport of water deeper into the vascular tree through changes in T2 than the used crusher gradients could, with their limited b‐value. Conclusion: Of the implemented techniques, TRUST allowed us to follow intravascular signal deeper into the vascular tree than the approach with (relatively weak) crusher gradients when quantifying the transport time of water across the blood–brain barrier.